Electrochemical Reduction of CO2 over Heterogeneous Catalysts in Aqueous Solution: Recent Progress and Perspectives. Issue 3 (12th December 2018) - Long, Chang; Li, Xiang; Guo, Jun; Shi, Yanan; Liu, Shaoqin; Tang, Zhiyong
Abstract: Electrochemical reduction of CO2 into value‐added chemicals or fuels, driven by renewable energy, presents a promising solution to depletion of fossil fuels and greenhouse effects caused by excessive carbon emissions. In the past few years, great efforts have been dedicated to promote research in this field. Herein, this review focuses on the recent advances of the underlying mechanistic studies and novel heterogeneous catalyst constructions for electrochemical reduction of CO2 in aqueous media, targeting at presenting a full landscape at the current stage. The outlook for the future development is also included at the end of this review. Abstract : Electrochemical reduction on heterogeneous catalysts in aqueous media provides a promising solution to depletion of fossil fuel uses and the greenhouse effect. Recent understanding for important products and advanced heterogeneous catalysts has been discussed.